The urban arboretum - Griesel, David (School of Architecture, Planning and Geomatics, 2018)
Trees in the urban fabric are often overlooked, and their significance in the effect of their presence that they hold is most often lost. Trees are seen as something of an afterthought, something purely aesthetic, or even something that poses a problem to the city instead of a solution to certain problems. Through my study project, the "Urban Arboretum", the objective is to explore all the different potential possibilities and opportunities that trees could have in the urban realm, not only pertaining to aesthetics, but also in terms of spatial and architectural qualities, as well as cultural connotations, and especially the productive and ecological potential that they hold. Through the study and understanding of these objectives they are applied to a chosen site through the concept of the dissertation which is "the Architecture of the Forest" This concept functions through the design and active maintenance of the scientific principles of succession of species.